An Academic Edition of a Russian Gothic Novel - Chernyshov, Maxim (Quaestio Rossica, 2021)
The book under review is an edition of the novel The Black Woman (1834) by the nineteenth-century Russian writer Nikolai Gretsch, part of the academic series “Literary Monuments”. It was prepared for publication by E. V. Markasova: the edition is supported by an extensive scholarly apparatus, including two supplemental texts from the 1830s, two scholarly articles, notes on the text, a chronicle of Gretsch’s life and work, a bibliography, and a list of illustrations. The reviewer evaluates the scholarly work of Markasova and her colleagues higher than the artistic quality of the novel itself, which suffers from the imperfections characteristic of early experiments in popular fiction. The reviewer believes that the aesthetic context in which Gretsch’s Gothic novel is considered must include not only genre, but also the artistic movements of the epoch, especially Romanticism. The lack of attention to this issue leads to some doubtful and controversial assertions in the notes concerning literary trends in the eighteenth and nineteenth centuries. At the end of the review, the author comes to the conclusion that academic studies are currently experiencing heightened interest in the mystical and irrational in literature.